Apresentações incomuns do hemangioma hepático: ensaio iconográfico - D'Ippolito, Giuseppe [UNIFESP] (2006)
In order to evaluate atypical aspects of hepatic hemangiomas at ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI), we have retrospectively analyzed 300 cases of patients diagnosed with hepatic hemangiomas by means of combined imaging studies, clinical follow-up and/or biopsy results. Based on this analysis we have selected those cases with atypical findings at one or more imaging methods or those presenting an unusual evolution such as: hypoechoic nodules at US; giant, heterogeneous hemangiomas; rapidly filling hemangiomas; calcified hemangiomas; pedunculated hemangiomas; hypointense hemangiomas at T2-weighted images; causing perfusion defect; with central scar simulating focal nodular hyperplasia; hemangiomas with adjacent abnormalities such as arterial-portal venous shunt and capsular retraction as well as hemangiomas enlarging over time. The hepatic hemangioma is the most common benign tumor affecting the liver and usually presents typical aspect. However, atypical findings should be known aiming at supporting diagnosis guidance and clinical decisions.